TRANSFORMASI PEMBELAJARAN SANTRI: OPTIMALISASI MEANINGFUL LEARNING MELALUI MODEL EXPERIENTIAL LEARNING (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Learning in Islamic boarding schools is often dominated by routine activities that are not always internalized meaningfully by students. This condition indicates the need for a learning model that is able to connect knowledge with real-life experiences in order to enhance meaningful learning. This study aims to analyze the implementation of the Experiential Learning model and its role in improving meaningful learning among students at Manarul Qur’an Islamic Boarding School. This research employed a qualitative approach with a descriptive design. Data were collected through in-depth interviews, participatory observation, and documentation involving teachers and students as research participants. The data were analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the Experiential Learning model was implemented through stages of concrete experience, reflective observation, abstract conceptualization, and active experimentation integrated into students’ daily religious and social activities. The implementation of this model contributed to the enhancement of meaningful learning as indicated by students’ improved understanding of learning objectives, their ability to relate learning materials to real-life experiences, and the internalization of Islamic values in their attitudes and behaviors. Therefore, Experiential Learning can serve as an effective pedagogical approach in fostering contextual, reflective, and spiritually meaningful learning in Islamic boarding school education